Multiphase customized rapid precipitation strengthening method for high-strength aluminum alloy

By performing solid solution quenching, pre-deforming and pre-aging treatment in high-strength aluminum alloys, forming and converting the reinforced phases, the problems of cumbersome heat treatment processes and long cycles in the prior art are solved, and rapid heat treatment and performance improvement of multiphase aluminum alloys are achieved.

CN119876799APending Publication Date: 2025-04-25WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510097649.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing multiphase high-strength aluminum alloy heat treatment process is complicated to operate and has a long period, resulting in insufficient yield strength and insufficient yield strength ratio.

Method used

High-strength aluminum alloy multi-phase customization rapid precipitation strengthening method is adopted, including solid solution quenching, pre-deforming and pre-aging treatment, to form a pioneer strengthening phase, and convert it into the main strengthening phase during the final aging treatment, with the total time being controlled within 17 hours.

Benefits of technology

The rapid heat treatment of multiphase aluminum alloy is realized, the process flow is simplified, the processing cycle is shortened, and the Quqiang ratio and service performance are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876799A_ABST
    Figure CN119876799A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum alloy thermal deformation, and particularly discloses a high-strength aluminum alloy multiphase customized rapid precipitation strengthening method which comprises the following steps: carrying out solid solution quenching treatment on a to-be-treated multiphase aluminum alloy to obtain a solid solution state plate, carrying out pre-deformation treatment on the solid solution state plate, and then carrying out pre-aging treatment to obtain a primary strengthened plate; wherein the temperature of the pre-aging treatment is the precipitation temperature of a precursor strengthening phase; and finally, final aging treatment is conducted on the primary strengthening plate to obtain a final strengthening plate, then strengthening is completed, and the final aging treatment temperature is the precipitation temperature of the main strengthening phase. Based on the characteristics of precipitation behaviors and evolution behaviors of multiple strengthening phases, the customized precipitation of the main strengthening phase is realized by breaking through a lengthy artificial aging inertia mode, so that the heat treatment period can be effectively shortened, and complex processes such as vibration and stress fields do not need to be combined; and meanwhile, the yield ratio and the service performance of the multiphase high-strength aluminum alloy can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of aluminum alloy thermal deformation, and more specifically, to a method for customized rapid precipitation strengthening of high-strength aluminum alloy multiphase. Background Art

[0002] High-strength aluminum alloy refers to a type of aluminum alloy material that is based on aluminum and has high strength by reasonably adding alloying elements (such as copper, magnesium, zinc, etc.) and optimizing processing technology (such as heat treatment, cold processing, etc.). It has always been a hot topic of long-term close attention in various industries, especially multi-phase high-strength aluminum alloys with multiple precipitation and evolution of strengthening phases. High-strength aluminum alloys have become the focus of research in aerospace and other fields due to their advantages such as low density, high specific strength, high specific modulus, good corrosion resistance and damage tolerance. However, in order to make its performance meet the service requirements, multi-phase high-strength aluminum alloys currently need to undergo a long period of deformation heat treatment, but there is still a problem of insufficient yield strength, which leads to insufficient yield strength ratio. The yield strength ratio is the ratio of yield strength to tensile strength. The yield strength ratio of aluminum alloys is roughly in the range of 0.8 to 0.9, which can reflect the ability of aluminum alloy components to resist deformation and fracture when subjected to external forces.

[0003] In the prior art, CN117004894A discloses an efficient aluminum-lithium alloy aging method based on dynamic strain precipitation. This method uses one-step temperature-controlled and speed-controlled hot rolling instead of cold deformation processing to form a dual distribution form in which the strengthening phase Al2CuLi is concentrated on the dislocation cell wall and uniformly distributed in the dislocation cell. Although it helps to improve the comprehensive mechanical properties of the alloy, the preheating, temperature-controlled and speed-controlled hot rolling processes of this method are relatively cumbersome, and the overall process cycle will also be extended. CN116005086A discloses a heat treatment process for improving the strength of aluminum-lithium alloys. Although this patent uses vibration to generate a small amount of plastic deformation to introduce dislocations to provide a large number of uniform nucleation points for the precipitation of T1 (Al2CuLi) strengthening phases, which significantly improves the strength of aluminum-lithium alloys, it needs to add a complex vibration process, and the required artificial aging time is relatively long, 13h to 18h. CN112981284A discloses a method for preparing a stress-aged high-strength aluminum-lithium alloy. Although this method achieves the best performance by controlling the pre-deformation amount, the stress field and the temperature field distribution in the heat treatment to achieve the comprehensive regulation of the type, quantity and size distribution of the precipitated phase in the aluminum-lithium alloy, its artificial aging process requires additional stress field. CN11676431A discloses a two-stage continuous aging treatment method for aluminum-lithium alloy. This method performs aging treatment on the aluminum alloy during the continuous temperature change, but it is necessary to strictly control the temperature rise rate of the two aging stages, and the overall aging time also requires more than 20 hours. CN113699471A discloses a discontinuous aging treatment method for AA2195 aluminum-lithium alloy. This method allows the material to form more strengthening phase precursor GP zones in the pre-aging and natural aging stages, so that the material presents a bimodal distribution of Al2Cu and Al2CuLi after the subsequent artificial aging process. Compared with the T8 alloy, more Al2Cu appears in the material, which increases the average size of the strengthening phase of the material and improves the strength of the material. However, this method includes many steps (solid solution, pre-aging, pre-deformation, low-temperature aging, aging), and the overall aging treatment time period is too long.

[0004] It can be seen from the existing patents that the optimization methods of the deformation heat treatment process for multi-strengthening phase aluminum alloys represented by aluminum-lithium alloys are, on the one hand, based on the form of pre-deformation, such as hot rolling (CN117004894A) and vibration (CN116005086A). These methods are too cumbersome to operate and consume extra energy; on the other hand, they are based on aging treatment, such as combined stress field (CN112981284A), variable temperature aging (CN11676431A), and multi-stage aging (CN113699471A). The overall aging treatment time cycle of these methods is relatively long. Summary of the invention

[0005] In view of the defects of the prior art, the present application provides a customized rapid precipitation strengthening method for multiphase high-strength aluminum alloys, aiming to solve the problems of cumbersome operation and long cycle of the existing multiphase aluminum alloy heat treatment process.

[0006] The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method provided in this application specifically includes: S1 performs solid solution quenching treatment on the multiphase aluminum alloy to obtain a solid solution state plate; S2 performs a pre-deformation treatment on the solid solution state plate; S3: performing a pre-aging treatment on the solid solution state plate after the pre-deformation treatment to obtain a primary strengthened plate, wherein the temperature of the pre-aging treatment is the precipitation temperature of the precursor strengthening phase; S4 performs final aging treatment on the primary strengthened plate to obtain a final strengthened plate, thereby completing the strengthening, wherein the temperature of the final aging treatment is the precipitation temperature of the main strengthening phase, and the total duration of the pre-deformation treatment, the pre-aging treatment and the final aging treatment is ensured to be within 17 hours.

[0007] Through the above technical scheme conceived by the present application, compared with the prior art, the present application forms different precursor strengthening phases inside the multi-phase aluminum alloy through solid solution quenching, pre-deformation and pre-aging treatment, and converts the precursor strengthening phases into main strengthening phases during final aging treatment. The heat treatment of the multi-phase aluminum alloy can be completed within 17 hours, and there is no need to combine complex processes such as vibration and stress field. It has the advantages of simple process and short cycle.

[0008] As further preferred, the multi-phase aluminum alloy includes aluminum-lithium alloy, aluminum-copper-magnesium alloy or aluminum-zinc-silicon alloy.

[0009] As a further preferred embodiment, in step S2, a tensile deformation of 3% to 7% is performed along the rolling direction of the solid solution state plate to achieve pre-deformation treatment.

[0010] As further preferred, in step S2, the pre-deformation treatment time is 5 minutes to 10 minutes.

[0011] As further preferred, in step S3, the pre-aging treatment time is 8 h to 16 h.

[0012] As further preferred, in step S4, the time of the final aging treatment is 3 min to 10 min.

[0013] As a further preference, the time intervals between the pre-deformation treatment, the solution hardening treatment and the pre-aging treatment are no more than 30 minutes.

[0014] As a further preference, the temperatures of the pre-aging treatment and the final aging treatment are determined according to the differential scanning calorimetry results of the solid solution plate and the primary strengthened plate.

[0015] As a further preferred method, the temperature determination method for the pre-aging treatment and the final aging treatment is: (a) The solid solution plate was analyzed by differential scanning calorimetry to obtain the precipitation temperature of the precursor strengthening phase and the main strengthening phase, and the precipitation temperature of the precursor strengthening phase was used as the pre-aging treatment temperature; (b) The primary strengthening plate was analyzed by differential scanning calorimetry to obtain the precipitation temperature of the updated main strengthening phase, and the updated precipitation temperature of the main strengthening phase was used as the final aging treatment temperature.

[0016] As a further preferred embodiment, it is determined whether the mechanical properties and yield strength ratio of the primary reinforced plate meet the requirements. If so, the final aging treatment is omitted; if not, the final aging treatment is performed.

[0017] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: 1. Based on the precipitation behavior and evolution behavior characteristics of multiple strengthening phases, this application breaks the lengthy artificial aging inertia mode, forms different precursor strengthening phases inside the multiphase aluminum alloy through solution quenching, pre-deformation and pre-aging treatment, and converts the precursor strengthening phase into the main strengthening phase during the final aging treatment, thereby realizing customized precipitation of the main strengthening phase, thereby effectively shortening the heat treatment cycle, completing the heat treatment of the multiphase aluminum alloy within 17 hours, and does not need to be combined with complex processes such as vibration and stress field, with the advantages of simple process and short cycle, and can significantly improve the yield strength ratio and service performance of the multiphase high-strength aluminum alloy; 2. At the same time, this application can shorten the heat treatment cycle while ensuring the treatment effect by optimizing the time of pre-deformation treatment, pre-aging treatment and final aging treatment; 3. In particular, the present application can further improve the treatment efficiency and treatment effect by optimizing the determination method of the pre-aging treatment temperature and the final aging treatment temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a process roadmap of a high-strength aluminum alloy multiphase customized rapid precipitation strengthening method provided in an embodiment of the present application; Figure 2 It is a schematic diagram of the heat treatment route of high-strength aluminum alloy in the prior art; Figure 3 Schematic diagram of two evolution routes of precipitated phases provided in the embodiments of the present application, wherein route 1 is to form a certain amount of θ′ phase and δ′ phase and a small amount of fine T1 phase with a thickness of about 1-2 nm after pre-aging, and route 2 is to form fine θ′ phase and δ′ phase after pre-aging; Figure 4This is a microstructure diagram of the final reinforced plate obtained in Example 2 of the present application; Figure 5 is a DSC curve of a solid solution 2A97 aluminum-lithium alloy provided in an embodiment of the present application; Figure 6 It is the DSC curve of the primary reinforced plate provided in the embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0020] like Figure 1 As shown, the present application provides a high-strength aluminum alloy multiphase customized rapid precipitation strengthening method, which specifically includes: S1 performs solid solution quenching treatment on the multiphase aluminum alloy to obtain a solid solution state plate; S2 performs pre-deformation treatment on the solid solution state plate; S3: performing a pre-aging treatment on the solid solution state plate after the pre-deformation treatment to obtain a primary strengthened plate, wherein the temperature of the pre-aging treatment is the precipitation temperature of the precursor strengthening phase; S4 performs final aging treatment on the primary strengthened plate to obtain the final strengthened plate, thereby completing the strengthening, wherein the temperature of the final aging treatment is the precipitation temperature of the main strengthening phase, and the total duration of the pre-deformation treatment, pre-aging treatment and final aging treatment is ensured to be within 17 hours.

[0021] Precipitation strengthening is an important strengthening mechanism of aluminum alloys. The strengthening phase that contributes most to strength is the main strengthening phase, and the strengthening phase that contributes less to strength and precipitates before the main strengthening phase is the pioneer strengthening phase. The present application forms different pioneer strengthening phases inside the multiphase aluminum alloy through solution quenching, pre-deformation and pre-aging treatments, and converts the pioneer strengthening phases into the main strengthening phase during the final aging treatment, thereby regulating the precipitation evolution behavior of different pioneer strengthening phases to the main strengthening phase, and achieving multi-phase customized rapid precipitation of strengthening phases in high-strength aluminum alloys. Finally, by strictly regulating the precipitation behavior of multiple strengthening phases in high-strength multiphase aluminum alloys at each stage, the heat treatment cycle of the high-strength aluminum alloy is effectively controlled within 17 hours, which is shorter than that of the above-mentioned. Figure 2 The existing heat treatment method (>36h) of multiphase aluminum alloys shown in the figure has a significant simplification effect and does not require the combination of complex processes such as vibration and stress field. It has the advantages of simple process and short cycle, and can significantly improve the yield strength ratio and service performance of multiphase aluminum alloys.

[0022] Taking aluminum-lithium alloy as an example, a certain number of precursor secondary strengthening phases δ′(Al2Cu) phase and θ′(Al3Li) phase are formed in the annealed aluminum-lithium alloy structure through solution quenching, pre-deformation and pre-aging treatment. The increase of dislocations in the pre-deformation process provides more nucleation sites for the subsequent precipitation of the main strengthening phase T1(Al2CuLi) phase; at the same time, rapid final aging for 3min to 10min in the precipitation temperature range of T1 phase (200℃~250℃) can realize the transformation of δ′ phase and θ′ phase to T1 phase in the aluminum-lithium alloy, forming a mode dominated by nanoscale main strengthening phase T1 phase, thereby ensuring the excellent yield strength ratio and fatigue resistance of aluminum-lithium alloy. The introduction of pre-deformation can not only provide more nucleation sites for the precipitation of T1 phase, but also improve the fatigue resistance of the material to a certain extent. Under this condition, taking aluminum-lithium alloy as an example, the tensile strength and yield strength can reach 595MPa and 565MPa respectively, the yield strength ratio is as high as 95%, and the entire heat treatment process cycle is shortened by 65% ​​to 75%.

[0023] Furthermore, a multiphase aluminum alloy is an aluminum alloy having multiple chemical components and a second phase with different strength contributions, wherein a certain strengthening phase has the highest relative strength contribution, including but not limited to aluminum-lithium alloy, aluminum-copper-magnesium alloy or aluminum-zinc-silicon alloy.

[0024] Furthermore, in step S1, the multiphase aluminum alloy to be treated may be subjected to a solution quenching treatment process commonly used in the prior art. In a preferred embodiment of the present application, for aluminum-lithium alloy, the specific process of the solution quenching treatment is to heat at 520°C for 90 minutes and then immediately quench to obtain a solid solution state plate.

[0025] Furthermore, in step S2, a 3% to 7% tensile deformation is performed along the rolling direction of the solid solution state plate to achieve pre-deformation treatment. The introduction of pre-deformation can provide more nucleation sites for the precipitation of the main strengthening phase, and improve the fatigue resistance of the material to a certain extent. At the same time, it can provide additional driving force for atomic diffusion and reaction during the aging process, prompting the strengthening phase to precipitate and grow faster and shorten the aging time. Excessive pre-deformation will reach saturation in the effect of improving the aging kinetics of aluminum alloys, and too small pre-deformation will produce a small number of dislocations, which is easy to cause insufficient precipitation of strengthening phases and insufficient structural transformation. Therefore, the deformation amount is preferably 3% to 7%.

[0026] Further, in step S2, the time of pre-deformation treatment is 5min to 10min. In step S3, the time of pre-aging treatment is 8h to 16h. If the pre-aging treatment time is too long, it is easy to cause the growth and coarsening of the precursor strengthening phase, weaken the hindering effect on dislocation movement, and reduce the strength of the primary strengthening aluminum alloy; if the pre-aging time is insufficient, the solute atoms fail to fully aggregate and nucleate, the number of precursor strengthening phases precipitated is small and the size is small, and the main strengthening phase cannot be quickly precipitated in the final aging step. In step S4, the time of final aging treatment is 3min to 10min. If the holding time is too long, the main strengthening phase will further transform into a non-strengthening phase, and at the same time, it will cause coarse grains, reducing the strength and fatigue life of aluminum alloy components; if the holding time is insufficient, the main strengthening phase transformation and growth time is insufficient, and the main strengthening phase of a certain size and quantity distribution cannot be formed, which will also lead to a reduction in the strength and fatigue life of aluminum alloy components.

[0027] Furthermore, the time intervals between the pre-deformation treatment, the solution quenching treatment and the pre-aging treatment should not exceed 30 minutes, respectively, to prevent natural aging due to long storage time, which would affect the subsequent aging effect.

[0028] Furthermore, the temperatures of the pre-aging treatment and the final aging treatment are determined according to the differential scanning calorimetry (DSC) results of the solid solution plate and the primary strengthening plate, specifically: (a) The solid solution plate was analyzed by differential scanning calorimetry to obtain the precipitation temperature of the precursor strengthening phase and the main strengthening phase, and the precipitation temperature of the precursor strengthening phase was used as the pre-aging treatment temperature; (b) The primary strengthening plate was analyzed by differential scanning calorimetry to obtain the precipitation temperature of the updated main strengthening phase, and the updated precipitation temperature of the main strengthening phase was used as the final aging treatment temperature.

[0029] Preferably, in step (a), the precipitation temperatures of multiple precursor strengthening phases can be obtained according to the DSC results, and the temperature range formed by them is used as the temperature range for pre-aging treatment. In step (b), the temperature range from ±10°C of the precipitation start temperature of the updated main strengthening phase to ±10°C of the exothermic peak temperature is used as the temperature range for final aging treatment.

[0030] Taking aluminum-lithium alloy as an example, DSC analysis was performed on 2A97 aluminum-lithium alloy after solution treatment at 520℃ / 90min. The results are as follows: Figure 5As shown, PeakA corresponds to the exothermic peak of precipitation in the GP zone, PeakB corresponds to the exothermic peak of precipitation of δ′ phase and θ′ phase, and PeakC corresponds to the exothermic peak of precipitation of T1 phase. For the solid solution 2A97 aluminum-lithium alloy, the exothermic peak at about 80°C is the precipitation in the GP zone, the exothermic peak at about 160-180°C corresponds to the precipitation of δ′ (Al3Li) and θ′ phase (Al2Cu), and the exothermic peak at about 275°C corresponds to the precipitation of T1 (Al2CuLi). Therefore, the temperature range of the pre-aging treatment is 80-180°C. Then, DSC analysis was performed on the primary strengthened aluminum alloy after deformation heat treatment. The results are shown in Figure 6 As shown, W represents solid solution, D represents the deformation amount of pre-deformation, and PA represents the pre-aging treatment time. For example, D7PA8 is 7% pre-deformation and 8 hours pre-aging. For 2A97 aluminum-lithium alloy after thermomechanical treatment, it is found that the precipitation exothermic peak of the main strengthening phase T1 shifts to the left and is located at about 250°C, while the temperature at which the T1 phase begins to precipitate corresponds to about 200°C. The results show that thermomechanical treatment helps promote the precipitation of the main strengthening phase T1, so the temperature range of the final aging treatment is 200-250°C.

[0031] Further, it is determined whether the mechanical properties and yield strength ratio of the primary strengthening plate meet the requirements. If the requirements are met, the final aging treatment is omitted. If the requirements are not met, the final aging treatment is performed, wherein the mechanical properties include tensile strength and yield strength. The specific requirements for mechanical properties and yield strength ratio can be set according to actual needs, and this application does not limit them. In practical applications, for primary strengthening plates that meet the requirements, it can be decided whether to perform the final aging treatment according to actual needs. If you want to obtain higher strength, you can continue to perform the final aging treatment. If you want to simplify the process, you can omit the final aging treatment.

[0032] like Figure 3 As shown, the high-strength aluminum alloy multiphase customized rapid precipitation strengthening method provided by the present application has two strengthening paths. Path 1 forms a certain number of θ′ phases and δ′ phases and a small amount of fine T1 phases with a thickness of about 1-2nm after pre-aging. After final aging, the δ′ phases and θ′ phases transform into the T1 phase, forming a pattern dominated by the nanoscale main strengthening phase T1 phase. Under this path, if the mechanical properties and yield strength ratio of the primary strengthened plate obtained after pre-aging treatment meet the requirements, the final aging process can be omitted. If you want to obtain a better strengthening effect, you can still perform the final aging treatment. Path 2 forms fine θ′ phases and δ′ phases after pre-aging. After final aging, the δ′ phases and θ′ phases transform into the T1 phase, forming a pattern dominated by the nanoscale main strengthening phase T1 phase. Under this path, the final aging process cannot be omitted.

[0033] The technical solution provided in this application is further described below based on specific embodiments.

[0034] Example 1 (1) The aluminum-lithium alloy is placed in a resistance heating furnace for solution treatment at 520 °C / 90 min and immediately water quenched to obtain a solution state plate; (2) Within 30 minutes, the solid solution state plate is subjected to a 7% pre-stretching deformation treatment along the sheet rolling direction; (3) Within 30 minutes, the pre-deformed solid solution state plate is subjected to a pre-aging treatment at 160°C / 12h in a constant temperature blast drying oven to obtain a primary strengthening plate. At this stage, a certain amount of θ′ phase and δ′ phase and a small amount of fine T1 phase with a thickness of about 1-2nm are formed inside the aluminum-lithium alloy, such as Figure 3 As shown in (a); (4) After the pre-aging treatment, the primary strengthened sheet is subjected to a final aging treatment at 200 °C / 3 min in a constant temperature drying oven to obtain a final strengthened sheet.

[0035] Microscopic analysis of the final strengthened plate shows that there is a large amount of dense and evenly distributed T1 phase inside it, which is easy to precipitate near dislocations.

[0036] According to the national standard "Tensile Test of Metal Materials Part 1: Room Temperature Test Method: GB / T 228.1-2021", a uniaxial tensile test was carried out to obtain the mechanical properties after forming. The average value of multiple tensile specimens was taken. The tensile strength can reach 595MPa, the yield strength can reach 565MPa, and the yield strength ratio can reach 95%.

[0037] Example 2 (1) placing the aluminum-lithium alloy in a resistance heating furnace for solution treatment at 520°C for 90 min and immediately water quenching to obtain a solid solution multiphase aluminum alloy; (2) within 30 minutes, the solid solution multiphase aluminum alloy is subjected to a 7% pre-stretching deformation treatment along the sheet rolling direction; (3) Within 30 min, the pre-deformed solid solution multiphase aluminum alloy is subjected to 80°C / 16 h pre-aging treatment in a blast constant temperature drying oven to obtain a primary strengthened aluminum alloy. During this stage, a certain amount of θ′ phase and δ′ phase are formed inside the aluminum-lithium alloy, such as Figure 3 As shown in (b); (4) After the pre-aging treatment, the primary strengthened aluminum alloy is subjected to a final aging treatment at 250 °C / 10 min in a blast constant temperature drying oven to obtain a final precipitation sheet.

[0038] After forming, microscopic analysis is performed, such as Figure 4 As shown, there are a large number of dense and evenly distributed T1 phases inside, and the average length of the main strengthening phase is only 62 nm, thus forming a nanoscale main strengthening phase, which is easy to precipitate near dislocations.

[0039] According to the national standard "Tensile Test of Metal Materials Part 1: Room Temperature Test Method: GB / T 228.1-2021", a uniaxial tensile test was carried out to obtain the mechanical properties after forming. The average value of multiple tensile specimens was taken. The tensile strength can reach 565MPa, the yield strength can reach 531MPa, and the yield strength ratio is as high as 94%.

[0040] Example 3 (1) The aluminum-lithium alloy is placed in a resistance heating furnace for solution treatment at 520 °C / 90 min and immediately water quenched to obtain a solution state plate; (2) Within 30 minutes, the solid solution state plate is subjected to a 7% pre-stretching deformation treatment along the sheet rolling direction; (3) Within 30 minutes, the pre-deformed solid solution state plate is subjected to a pre-aging treatment at 100°C / 8h in a blast constant temperature drying oven to obtain a primary strengthening plate. During this stage, a certain amount of θ′ phase and δ′ phase are formed inside the aluminum-lithium alloy, such as Figure 3 As shown in (b); (4) After the pre-aging treatment, the primary strengthened sheet is subjected to a final aging treatment at 200 °C / 5 min in a constant temperature drying oven to obtain a final strengthened sheet.

[0041] Microscopic analysis of the final strengthened plate shows that there are a large number of dense and evenly distributed nanoscale T1 phases inside it, which are easy to precipitate near dislocations.

[0042] According to the national standard "Tensile Test of Metal Materials Part 1: Room Temperature Test Method: GB / T 228.1-2021", a uniaxial tensile test was carried out to obtain the mechanical properties after forming. The average value of multiple tensile specimens was taken, and the tensile strength could reach 566MPa and the yield strength could reach 519MPa.

[0043] Example 4 (1) The aluminum-lithium alloy is placed in a resistance heating furnace for solution treatment at 520 °C / 90 min and immediately water quenched to obtain a solution state plate; (2) Within 30 minutes, the solid solution state plate is subjected to a 7% pre-stretching deformation treatment along the sheet rolling direction; (3) Within 30 minutes, the pre-deformed solid solution state plate is subjected to a pre-aging treatment at 160°C / 14h in a blast constant temperature drying oven to obtain a primary strengthened plate, such as Figure 3 As shown in (a), at this stage, a certain amount of θ′ phase and δ′ phase and a small amount of fine T1 phase with a thickness of about 1nm to 2nm are formed inside the aluminum-lithium alloy; (4) After the pre-aging treatment, the primary strengthening plate is subjected to a final aging treatment at 200 °C / 3 min in a constant temperature drying oven.

[0044] Microscopic analysis after forming shows that there are a large number of dense and evenly distributed T1 phases inside, which are easy to precipitate near dislocations.

[0045] According to the national standard "Tensile Test of Metal Materials Part 1: Room Temperature Test Method: GB / T 228.1-2021", a uniaxial tensile test was carried out to obtain the mechanical properties after forming. The average value of multiple tensile specimens was taken. The tensile strength can reach 608MPa, the yield strength can reach 544MPa, and the yield strength ratio is 89%.

[0046] Example 5 (1) placing the aluminum-lithium alloy in a resistance heating furnace for solution treatment at 520°C / 90 min and immediately quenching with water to obtain a solution state plate; (2) Within 30 minutes, the solid solution plate is subjected to a 7% pre-stretching deformation treatment along the rolling direction of the plate; (3) Within 30 minutes, the pre-deformed solid solution state plate is subjected to a pre-aging treatment at 160°C / 16h in a constant temperature blast drying oven to obtain a primary strengthened plate. The mechanical properties and yield strength ratio of the primary strengthened plate meet the requirements, and strengthening is completed.

[0047] The primary reinforced plate was subjected to a tensile test. According to the national standard "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method: GB / T 228.1-2021", a uniaxial tensile test was performed to obtain its mechanical properties after pre-aging. The average value of multiple tensile specimens was taken. The tensile strength can reach 585MPa, the yield strength can reach 552MPa, and the yield strength ratio is 94%. Example 6 (1) placing the aluminum-lithium alloy in a resistance heating furnace for solution treatment at 520°C / 90 min and immediately quenching with water to obtain a solution state plate; (2) Within 30 minutes, the solid solution state plate is subjected to a 7% pre-stretching deformation treatment along the sheet rolling direction; (3) Within 30 minutes, the pre-deformed solid solution state plate is subjected to a pre-aging treatment at 160°C / 12h in a blast constant temperature drying oven to obtain a primary strengthened plate; (4) After the pre-aging treatment, the primary reinforced sheet is heated to 250°C in a constant temperature drying oven and kept at this temperature for 5 minutes to obtain the final reinforced sheet.

[0048] The final reinforced plate was subjected to low-cycle tension and compression fatigue tests using an Instron 1341 electro-hydraulic servo universal material testing machine. The test was conducted in strict accordance with the national standard GB / T 26077-2021. Take multiple samples at 0.5% and take the average value. =0.5% and the fatigue life is 2100 times.

[0049] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the feature. In the description of the present application, "plurality" means two or more, unless otherwise clearly and specifically defined.

[0050] In addition, references throughout this specification to "one embodiment"; "one embodiment", "an example" or similar language indicate that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present application. Thus, appearances of the phrase "in one embodiment"; "in one embodiment" and similar language throughout this specification may, but do not necessarily, all refer to the same embodiment.

[0051] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A multiphase customized rapid precipitation strengthening method for high-strength aluminum alloy, characterized in that: Specifically include: S1 performs solid solution quenching treatment on the multiphase aluminum alloy to obtain a solid solution state plate; S2 performs a pre-deformation treatment on the solid solution state plate; S3: performing a pre-aging treatment on the solid solution state plate after the pre-deformation treatment to obtain a primary strengthened plate, wherein the temperature of the pre-aging treatment is the precipitation temperature of the precursor strengthening phase; S4 performs final aging treatment on the primary strengthened plate to obtain a final strengthened plate, thereby completing the strengthening, wherein the temperature of the final aging treatment is the precipitation temperature of the main strengthening phase, and the total duration of the pre-deformation treatment, the pre-aging treatment and the final aging treatment is ensured to be within 17 hours.

2. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 1, characterized in that: The multi-phase aluminum alloy includes an aluminum-lithium alloy, an aluminum-copper-magnesium alloy or an aluminum-zinc-silicon alloy.

3. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 1, characterized in that: In step S2, a tensile deformation of 3% to 7% is performed along the rolling direction of the solid solution state plate to achieve pre-deformation treatment.

4. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 1, characterized in that: In step S2, the pre-deformation treatment time is 5 minutes to 10 minutes.

5. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 1, characterized in that: In step S3, the pre-aging treatment time is 8 hours to 16 hours.

6. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 1, characterized in that: In step S4, the final aging treatment time is 3 minutes to 10 minutes.

7. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 1, characterized in that: The time interval between pre-deformation treatment, solution quenching treatment and pre-aging treatment shall not exceed 30 minutes.

8. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to any one of claims 1 to 7, characterized in that: The temperatures of the pre-aging treatment and the final aging treatment are determined based on the differential scanning calorimetry results of the solid solution plate and the primary strengthening plate.

9. The high-strength aluminum alloy multiphase customized rapid precipitation strengthening method according to claim 8, characterized in that: The temperature determination method for pre-aging treatment and final aging treatment is: (a) The solid solution plate was analyzed by differential scanning calorimetry to obtain the precipitation temperature of the precursor strengthening phase and the main strengthening phase, and the precipitation temperature of the precursor strengthening phase was used as the pre-aging treatment temperature; (b) The primary strengthening plate was analyzed by differential scanning calorimetry to obtain the precipitation temperature of the updated main strengthening phase, and the updated precipitation temperature of the main strengthening phase was used as the final aging treatment temperature.

10. The high-strength aluminum alloy multiphase customized rapid precipitation method according to any one of claims 1 to 9, characterized in that: It is judged whether the mechanical properties and yield strength ratio of the primary strengthened plate meet the requirements. If so, the final aging treatment is omitted; if not, the final aging treatment is performed.

Citation Information

Patent Citations

  • Preparation method of stress aging state high-strength aluminum lithium alloy

    CN112981284A

  • Interrupted aging treatment method for AA2195 aluminum lithium alloy

    CN113699471A

  • Heat treatment process for improving strength of aluminum-lithium alloy

    CN116005086A

  • Efficient aluminum-lithium alloy aging method based on dynamic strain precipitation

    CN117004894A